2016
DOI: 10.4028/www.scientific.net/msf.848.184
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Identification of Adulteration of Polycarbonate Drinking Bottles with Postconsumer Recycled Plastics

Abstract: Adulteration of polycarbonate (PC) drinking bottles with postconsumer recycled PC materials was considerably difficult to identify due to similar chemical compositions and minute differences between virgin and recycled PC materials. In the present study, UV/Vis spectroscopy coupled with GC-MS analysis was carried out to identify the adulteration with recycled materials in PC drinking bottles. The minimum adulterating level which could be detected was 20 %. This strategy represents a rapid and promising analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[8] There is not a specific authoritative method for the detection of the adulteration of plastic materials with less expensive recycled resins during manufacturing. Chromatographic approaches based on headspace-gas chromatography-mass spectrometry (HS-GC-MS), [6,9] microwave assisted extraction followed by GC-MS, [10] and ultra-performance-liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) [11] have been carried out with the purpose of discriminating between recycled and virgin plastics. In the same way, thermal analytical tools such as differential scanning calorimetry, thermal gravimetric, and melt flow index analyses have been applied to determine thermal polymer properties which vary between virgin and recycled polymers, being useful for authentication purposes.…”
Section: Introductionmentioning
confidence: 99%
“…[8] There is not a specific authoritative method for the detection of the adulteration of plastic materials with less expensive recycled resins during manufacturing. Chromatographic approaches based on headspace-gas chromatography-mass spectrometry (HS-GC-MS), [6,9] microwave assisted extraction followed by GC-MS, [10] and ultra-performance-liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) [11] have been carried out with the purpose of discriminating between recycled and virgin plastics. In the same way, thermal analytical tools such as differential scanning calorimetry, thermal gravimetric, and melt flow index analyses have been applied to determine thermal polymer properties which vary between virgin and recycled polymers, being useful for authentication purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Good adhesion can only be found between polymers of the same type (Kutz, 2011;Rosato et al, 2010). Wei et al (2016) reported that increasing the percentage of recycled HDPE decreased the tensile strength of the blend but increased the ductility. The study also reported the effect of the calcium carbonate filler on the mechanical properties and found that increasing its content, in general, deteriorated these properties.…”
Section: Introductionmentioning
confidence: 99%